An overview on biocatalysts immobilization on textiles: Preparation, progress and application in wastewater treatment. (September 2021) - Morshed, Mohammad Neaz; Behary, Nemeshwaree; Bouazizi, Nabil; Guan, Jinping; Nierstrasz, Vincent A.
Abstract: The immobilization of biocatalysts or other bioactive components often means their transformation from a soluble to an insoluble state by attaching them to a solid support material. Various types of fibrous textiles from both natural and synthetic sources have been studied as suitable support material for biocatalysts immobilization. Strength, inexpensiveness, high surface area, high porosity, pore size, availability in various forms, and simple preparation/functionalization techniques have made textiles a primary choice for various applications. This led to the concept of a new domain called-biocatalysts immobilization on textiles. By addressing the growing advancement in biocatalysts immobilization on textile, this study provides the first detailed overview on this topic based on the terms of preparation, progress, and application in wastewater treatment. The fundamental reason behind the necessity of biocatalysts immobilized textile as well as the potential preparation methods has been identified and discussed. The overall progress and performances of biocatalysts immobilized textile have been scrutinized and summarized based on the form of textile, catalytic activity, and various influencing factors. This review also highlighted the potential challenges and future considerations that can enhance the pervasive use of such immobilized biocatalysts in various sustainable and green chemistry applications. Graphical abstract: Image 1 Highlights: First overview on biocatalysts immobilization on textiles. Journey of biocatalysts immobilization on micro fibrous textiles to nanofibrous textiles. Biocatalysts immobilized textiles for environmental remediation application. Challenges, influencing factors and future considerations for biocatalysts immobilization on textiles.